Analisis Preferensi Siswa Melanjutkan Studi Ke Smk Muhammadiyah Kuok Tahun Pelajaran 2014/2015 - Cecep Imam Santoso Cecep Imam Santoso; Sardi Yusuf Sardi Yusuf; Rosmawa ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : One of the strategic policy which has arranged to widen the even distribution and the education access is to widen the accessto the education is SMK appropriate with the local necessity and superiority. The policy for improvement of quality, relevance, and educations capacity to compeleare done by program strengthening, such as school development based and local superiority in each regency or city in order to carry out the mandate of UU no. 20/2003. The improvement of quality and relevance in vocation at secondary school (SMK) done with developing the field of studies which appropriate to the jo words necessity and appropriate to the students interest. The pupose of the research is to identify the factor of what affects the peoples preferences in selecting SMK Muhammadiyah is Kuok city. The research is using descriptive quantitative research method. The analysis technique using tabulating analysis, it is a statistic analysis to find the amount of each variables influence with the peoples preference in selecting of studies in SMK Muhammadiyah in the Kuok city. From the banalysis of the factors of what affect to the students in selecting school, the result is school factor has biggest affect, then the location factor. In the other hand, statistic analysis has a result that there is a positive relationship between school selecting preference and economic condition. For recommendation of the research is that there is a need for upgrading the school quality and the availability of the instruments and infrastructure in SMK Muhammadiayh in Kuok city, so it will raise the peoples interest. Keywords : Analysis Preference